Catalytic hydrothermal deoxygenation of fatty acids over palladium on activated carbon catalyst (Pd/C) for renewable diesel production. Issue 9 (21st October 2021) - Edeh, Ifeanyichukwu; Overton, Tim; Bowra, Steve
Abstract: Renewable diesel, a potential substitute for petroleum diesel, is usually produced from biological sources by deoxygenating fatty acids in the presence of organic solvents with the addition of hydrogen. This could pose a health challenge and increase the cost of production. The current work was conducted in subcritical water without the addition of hydrogen using palmitic and oleic acids as fatty acids. The impact of temperature and reaction time was assessed using 5% palladium on activated carbon (Pd/C) catalyst. The recovered organic products were analysed for hydrocarbons using gas chromatography. The results show that the main hydrocarbon products from palmitic and oleic acids were pentadecane and heptadecane, respectively. The maximum value of the molar yield of pentadecane was 35.4% at the optimum conditions of 290 °C and 1.5 h, and that from heptadecane was 16.6% at 330 °C and 4 h. This shows that 5% Pd/C is active for catalysing the hydrothermal decarboxylation of the fatty acids to hydrocarbons. With these results, the cost of production can probably be reduced and the capacity to use hydrocarbons from a renewable resource to displace conventional diesel can be increased.